Prospects for Ukraine's participation in international trade in services - Schwodiauer, Gerchard; Necheporenko, D. A. (Національний технічний університет "Харківський політехнічний інститут", 2025)
The report determines that the prospects for Ukraine's participation in international trade in services look promising, especially in the context of the dynamic development of the IT sector and the growth of global demand for remote services. Success will depend on a country's ability to integrate into international networks, improve service quality, and meet international standards. Active state support, investments in human capital, as well as strengthening of the institutional and infrastructure base will allow Ukraine to take its rightful place in the global services market, which, in turn, will have a positive impact on the sustainable development of the national economy.
Перспективи участі України у міжнародній торгівлі послугами
Keywords: international trade; market; demand; supply; prospects; Ukraine; development; efficiency